Reengineering Vital Registration and Statistics Systems [Response to Letter] - Charles J. Rothwell (Centers for Disease Control and Prevention, 2005)
Dr Nasseri has registered valid concerns (1) about reengineering vital registration and statistics systems for the United States (2), many of which I share. Certainly the move to state-of-the-art information technology will not be the only key to rejuvenating the vital statistics system. We must not miss this opportunity to improve both the quality and the content of the information provided by these reengineered systems. The expanded data set derived from the new standard certificates, once implemented by the new systems, will improve data content extensively. These certificates are available on the Internet (3). Considerable work lies ahead in finding innovative ways to improve data quality for both new and old data items.